2015
DOI: 10.1186/s12885-015-1991-5
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative SUVmax for 18F-FDG uptake predicts survival in patients with colorectal cancer

Abstract: BackgroundThe study was to investigate whether 18F-fluorodeoxyglucose (18F-FDG) uptake, analyzed by positron emission tomography (PET), can be used preoperatively to predict survival in Chinese patients with colorectal carcinoma.MethodsA prospectively maintained colorectal cancer database was retrospectively reviewed between June 2009 and December 2011. All included patients had been newly diagnosed with colorectal cancer (of various stages) and evaluated by 18F-FDG-PET/computed tomography (CT) within the 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 35 publications
3
53
3
Order By: Relevance
“…Standard uptake values (SUV) and volume-based indices are most extensively investigated. In patients with colorectal cancer, these measures are demonstrated to be prognostic on pre-treatment [ 18 F]FDG PET in neoadjuvant [ 2 , 3 ] and metastatic settings [ 4 , 5 ]. However, the corrected tumour activity or metabolically active tumour volume (MATV) are only some of the PET characteristics which can be calculated from PET images.…”
Section: Introductionmentioning
confidence: 99%
“…Standard uptake values (SUV) and volume-based indices are most extensively investigated. In patients with colorectal cancer, these measures are demonstrated to be prognostic on pre-treatment [ 18 F]FDG PET in neoadjuvant [ 2 , 3 ] and metastatic settings [ 4 , 5 ]. However, the corrected tumour activity or metabolically active tumour volume (MATV) are only some of the PET characteristics which can be calculated from PET images.…”
Section: Introductionmentioning
confidence: 99%
“…PET-CT is one of the currently available noninvasive imaging methods and is widely used in the diagnosis and staging of malignant tumors or monitoring of chemotherapeutic response in patients with cancer. 26 Our results revealed that SUV max was significantly higher in MET-positive expression tumors than in MET-negative expression tumors, suggesting that 18 F-FDG accumulation may reflect MET expression in lung adenocarcinomas.…”
Section: Discussionmentioning
confidence: 51%
“…However, if systemic metastasis is definitely confirmed via an abdominopelvic or chest CT, adding 18 F-fluorodeoxyglucose ( 18 F-FDG) positron-emission tomography (PET) or 18 F-FDG-PET/CT for further clinical decision is controversial. Some studies have demonstrated that conventional PET-derived parameters, such as maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG), carry their own significance in stratifying survival of patients with CRC [5][6][7][8]. However, other studies yielded equivocal results [9,10].…”
Section: Introductionmentioning
confidence: 99%